A strategic plan for the Holy Infant School - Matalam, Amie P. (School of Management, University of the Philippines Mindanao, 2010)
The Holy Infant School is a Christian private school which offers a complete Pre-school, Elementary, High School and College education. It was founded by Mrs. Elizabeth Lopez in 1981.It has been operating for twenty-eight tears now. It has three campuses which are located in Jacinto, Mintal and Buhangin. Its College offerings are Nursing, Information Technology, Commerce and Education. As a Christian school, it aims to producing graduates who are excellent in academics and leaders who respond to God?s will. This paper used Fred David?s framework basis of evaluating the company?s Internal and External analysis. The four functional areas which are the Human Resource, Operations, Marketing and Finance are given focused in coming up with strategies. The environmental scanning resulted a positive result in the external factor with a rather small margin lag for the internal factor to be satisfactory. The company?s strengths include its location, growth opportunity for employees, demand for education is high, and its liquidity. Its weaknesses arte high teacher turn-over, lack of research and study for program implementation, and the annual decrease of enrollees. Organizational Development, having met the highest score in the QSPM is the strategy implemented. It is focused on the effectiveness of the organization and its people. Since the school continues to expand, it necessities changes that will meet its present needs. This paper identified the following strategic outcomes in the next five years: organizational structure, review of employees? compensation and benefits and extended course offerings in Mintal and Buhangin campuses.